The Impact of Contextual Teaching and Learning on Students’ Communication Skills - Akhmad Asyari; Muhamad Ahyar Rasidi (MEDIA DAN STRATEGI PEMBELAJARAN, 2026)
This study aimed to examine the effect of the Contextual Teaching and Learning (CTL) model on university students’ communication skills. The study employed a quasi-experimental method using a pretest–posttest control group design. The research subjects consisted of two classes: an experimental class implementing the CTL model and a control class using conventional instruction. The results showed that the mean pretest score of students’ communication skills in the experimental class was 66, while that of the control class was 63, indicating relatively equivalent initial abilities. After the treatment, the mean posttest score of the experimental class increased to 84, whereas the control class reached 71. The N-gain value of the experimental class was 0.50, categorized as moderate, while the control class obtained an N-gain of 0.23, categorized as low. Furthermore, an effect size of 0.82 indicated a large impact of the CTL model on students’ communication skills. Therefore, the CTL model is statistically and practically effective in improving university students’ communication skills.